Analysis of Silica-Hexadecyltrimethoxysilane Nanosol Hybrids through optimization of Silica Nanosol Concentration and determining fabric types on Hydrophobicity - Pereiz, Zimon; Chuchita, Chuchita; Oksal, Efriyana; Manurung, Stepanus Fredi (Universitas Wiralodra, 2024)
An analysis of the silica nanosol-hexadecyltrimethoxysilane hybrid has been carried out through optimizing the concentration of silica nanosol and determining the type of fabric regarding hydrophobicity. This research began with the synthesis of silica nanosol via the sol-gel method, where TEOS as a precursor was dissolved in a mixture of ethanol-distilled water with a base catalyst with a contact time of 2 hours. The concentration of silica nanosol was varied by 0.025, 0.05, and 0.075 mol. The dip-coating method was used to coat the fabric with nanosol, with a tensile rate of 3 cm per second. Then the fabric was re-coated with silica nanosol in HDTMS solution (4% wt/wt ethanol) and dried in a 120°C oven for 10 minutes. This research tested calico, cotton and mori fabrics. A Canon DSLR camera with a Thamron 100mm lens was used to measure the contact angle of the fabric surface. ImageJ software processes images to obtain contact angle values on the fabric surface. The fabric was then characterized using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM) and the silica nanosol was characterized using a Transmission Electron Microscope (TEM). The optimum concentration of silica-hdtms nanosol was obtained at a concentration of 0.075 mol with surface contact angles of cotton, mori and calico fabrics of 134, 132 and 135°. The flow speed of water with a slope of 100 on cotton, mori, and calico fabric produces flow speeds of 3.3, 6, and 5 m/s.